The Role of Strategic Foresight in Achieving Advanced Manufacturing Requirements: An Exploratory Study for the Managerial Leadership Opinions at Some Factories of the General Company for Food Products - Sultan, Hikmat; Ameen, Hinar (The Arab Journal of Administration, 2020)
The study aims to explore the correlation and effect relationship between the requirements of strategic foresight (strategic dialogue, strategic awareness, business intelligence, integration of capabilities) and the fulfillment of advanced manufacturing requirements (administrative requirements, technical requirements). The research presented the problem of study in a number of research questions; is there a clear idea about the practices of strategic foresight and advanced manufacturing? Do the factories in question have existing requirements for advanced manufacturing? In order to investigate the study problem, a number of hypotheses were formulated, including a correlation relationship and a significant effect of strategic foresight in achieving advanced manufacturing requirements. To address the study problem and test its hypotheses, a model was designed based on the requirements of strategic foresight as an independent variable and advanced manufacturing as a dependent variable. The analytical descriptive approach was applied by developing a questionnaire consisting of (46) paragraphs to study the requirements of strategic foresight and its relationship and its effect on advanced manufacturing in a sample of the factories of the general company for food products in Baghdad. The number of individuals surveyed was (162) administrative leaders in the inspected factories, Statistical methods were used to process, analyze and reach the results using the SPSS program (V. 23). Among these results are significant and positive levels of correlation between strategic foresight and advanced manufacturing in the investigated factories. In other words, the better the capabilities of the factories investigated in the strategic vision, the more efficient the factories will be able to meet the advanced manufacturing requirements. Finally, the study recommends strengthening the strategic dialogue in the investigated organizations with all stakeholders, especially its semployees; in order to achieve the objectives of the Organization and meeting the requirements of advanced manufacturing.